Znaczenie zmienności i poziomu inflacji dla kształtu empirycznej krzywej Phillipsa: The importance of inflation volatility and the shape of the empirical Phillips curve - Przekota, Grzegorz; Lisowska, Agnieszka (Management and Administration Journal, 2021)
Interchangeability of inflation and the unemployment rate allow for the effective use of monetary policy instruments. However, interchangeability is not always obvious. During certain times the empirical Phillips curve takes the form of agreement with the theoretical curve, and at other times the shape is different. This paper discusses the problem of variability and the importance of inflation for the shape of the empirical Phillips curve. Inserted are all the hypothesis that at a low level of unemployment, and with low inflation volatility, the concept of interchangeability will not be validated, and will be at higher levels of unemployment and higher inflation volatility. Hypothesis arises from the concept of the natural rate of unemployment.